2022
DOI: 10.1590/fst.56020
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted drying and extraction technique; kinetic modelling, energy consumption and influence on antioxidant compounds of fenugreek leaves

Abstract: Fenugreek leaves contains bioactive compounds, which are helpful in maintaining human health. These compounds are adversely affected in conventional drying methods. Therefore, this study was carried out to retain maximum amount of these components through microwave-assisted drying and extraction technique. The technique was optimized for simultaneous drying and extraction process for fenugreek leaves. The drying rate and drying time were influenced by the level of microwave power; time was reduced from 21 to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…By reducing this time, the energy consumption also decreased [49]. In a study by Azimi-Nejadian and Hoseini [47], a specific energy consumption between 0.68 to 2.59 MJ/kg was obtained for drying potatoes in a microwave dryer at power range of 200-800 W. In another study, Khan et al [50] reported specific energy consumption for drying fenugreek leaves in various MW powers (30 to 100 W) in the range of 1.86-2.47 MJ/kg. Furthermore, the energy required to remove one kilogram of water from the cantaloupe pieces during the microwave drying process significantly increased (with a probability level of 5%) by enhancing the thickness of the samples.…”
Section: Specific Energy Consumptionmentioning
confidence: 97%
“…By reducing this time, the energy consumption also decreased [49]. In a study by Azimi-Nejadian and Hoseini [47], a specific energy consumption between 0.68 to 2.59 MJ/kg was obtained for drying potatoes in a microwave dryer at power range of 200-800 W. In another study, Khan et al [50] reported specific energy consumption for drying fenugreek leaves in various MW powers (30 to 100 W) in the range of 1.86-2.47 MJ/kg. Furthermore, the energy required to remove one kilogram of water from the cantaloupe pieces during the microwave drying process significantly increased (with a probability level of 5%) by enhancing the thickness of the samples.…”
Section: Specific Energy Consumptionmentioning
confidence: 97%
“…Using drying techniques under environmental conditions is applicable only in the presence of favorable climates, i.e., in sunny and breezy areas such as tropical and sub-tropical countries where, moreover, the rural economy is still present [ 4 ]. Mild environmental temperatures prevent the loss of heat-sensitive compounds, but stabilization in this way can require long waiting times, which can favor increases in metabolic and enzymatic reactions in postharvest products, and also damages caused by weeds [ 4 , 5 ]. Moreover, large surfaces are needed and, finally, drying treatment could not be uniform, increasing the risk of contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Comfort for human beings was assessed from the viewpoints of Fanger's predicted mean vote (PMV) and predicted percentage of dissatisfied (PPD) [50,51]. Equations ( 18)- (22) were used to calculate the PMV and PPD.…”
Section: Human Thermal Comfort Indicesmentioning
confidence: 99%